Assessing the carbon reduction potential of municipal solid waste management transition: Effects of incineration, technology and sorting in Chinese cities - Wen Xiao; Tao Liu; Xin Tong (Resources, Conservation and Recycling, 2023)
The urban infrastructures of municipal solid waste (MSW) disposal play important roles in carbon reduction and building sustainable cities. China, with the world's largest MSW generation, has witnessed a relatively slow and spatially uneven transition progress of MSW disposal management. This study analysed the MSW disposal management transition and its determinants in Chinese cities of different sizes. Furthermore, the carbon reduction potential of MSW disposal management transition was estimated under different settings of policy reform. The results indicate that the MSW disposal management transition has made faster progress in cities with larger sizes, which could be ascribed to larger contradiction between city development and public service. The prediction results suggest that 73.13%–287.28% of carbon emission could be reduced by various policy reforms compared with the baseline scenario without policy intervention. Moreover, technological transformation should be specially underlined in mega cities, and household sorting should be specially underlined in medium cities.